Travel writing and re-enactment : echotourism - Tromly, Lucas, 1973- (New York, NY : Routledge, 2024)
"Travel Writing and Re-Enactment: Echotourism explores the popular subgenre of travel narratives that re-enact historically prominent journeys. Drawing on philosopher Walter Benjamin, this monograph reads such re-enactments as quests for aura in which travellers seek to capture a sense of distinction and historical profundity. Travel Writing and Re-Enactment frames the re-enactment of past journeys in a number of contexts, including Benjamin's writing on mechanical reproduction, Judith Butler's work on gender performance, and postmodern parody. Echotourist journeys are surprisingly contingent and precarious, and force travellers to navigate historical changes involving empire, gender, and travel practice in densely performative ways. Through close readings of contemporary travel narratives this monograph considers the legacies of Lord Byron, Charles Darwin, Graham Greene, Mary Kingsley, and Ernest Shackleton, among others. Travel Writing and Re-Enactment examines the way literary re-enactment expresses, and sometimes confounds, the desire to find meaning through travel in the contemporary world"--
Keywords: Travelers' writings, English -- History and criticism; Travelers' writings, American -- History and criticism; Travel in literature; PHILOSOPHY / History & Surveys / Modern